Analysis Bio-oil of Pyrolysis Production Process from Corn Cobs - Sri Aulia Novita; Perdana Putera; Musdar Effy Djinis; Yuni Ernita (Journal of Applied Agricultural Science and Technology, 2025)
Corn cobs are converted into bio-oil through pyrolysis using a simple pyrolysis apparatus at temperatures ranging from 300 to 400°C. This study evaluates the efficiency of the pyrolysis system, characterizes the compounds in corn cob bio-oil, and analyzes the economic viability of the method. The methods include the raw materials preparation (through drying and size reduction), development of bio-oil production equipment, implementation of pyrolysis and condensation processes, purification of the resulting bio-oil, compound analysis of the bio-oil, performance evaluation of the equipment, and engineering economic analysis. The successful production of high-quality bio-oil depends heavily on the precise and careful installation of all system components, including the pyrolysis reactor, smoke pipe, tar catcher, condenser, coil pipe, outlet pipe, liquid smoke container, water drum, and combustion furnace. The tool has a production capacity ranging from 0.89 to 0.96 kg per hour, with a coefficient of determination of 97.94%, and produced a yield of 32% to 34%. The bio-oil derived from corn cobs contained several compounds, including acetic acid, methyl ester, decenal, methyl 9,9-dideutero-octadecanal, phenol, 1-octanol, 2-butyl, 2-heptadecanone, myristaldehyde, octadecane, 1-chloro, and 1,9-tetradecadiene. The basic operating cost of the equipment is Rp 18,509.28 per kilogram, with a break-even point (BEP) of 238.43 kg per year. The basic production cost represents the minimum selling price required to achieve profitability. Biomass pyrolysis is a crucial thermal conversion technique with significant industrial and economic potential.